Understanding The Importance of Housekeeping Department In Boosting The Sale And Reputation of Hotel Industry - Nilesh Ratnoday; Naiya Rana (AG Volumes, 2021)
This research aimed for attaining a better understanding of the role and importance of housekeeping department. In addition, the role of housekeeping department in boosting the sale of the organization along with enhancing the reputation is also brought under study. To accomplish these objectives, 2 hypotheses were created based on which a questionnaire comprising of 14 questions were distributed among several individuals. 122 responses were received, which were samples and analyzed. The hypotheses were tested using one-way ANOVA and result showed a significant impact of housekeeping in boosting the sale and reputation of hotel industry.